The effectiveness of test-driven development approach on software projects: A multi-case study - Vahid Bakhtiary; Taghi Javdani Gandomani; Afshin Salajegheh (Institute of Advanced Engineering and Science, 2020)
Over recent years, software teams and companies have made attempts to achieve higher productivity and efficiency and get more success in the competitive market by employing proper software methods and practices. Test-driven development (TDD) is one of these practices. The literature review shows that this practice can lead to the improvement of the software development process. Existing empirical studies on TDD report different conclusions about its effects on quality and productivity. The present study tried to briefly report the results from a comparative multiple-case study of two software development projects where the effect of TDD within an industrial environment. Method: We conducted an experiment in an industrial case with 18 professionals. We measured TDD effectiveness in terms of team productivity and code quality. We also measured mood metric and cyclomatic complexity to compare our results with the literature. We have found that the test cases written for a TDD task have higher defect detection ability than test cases written for an incremental NON-TDD development task. Additionally, discovering bugs and fixing them became easier. The results obtained showed the TDD developers develop software code with a higher quality rate, and it results in increasing team productivity than NON_TDD developers.